Identification of the direction and value of the wave length of each mode for a rotating tire using the phase difference method. (February 2016) - Lee, Jongsuh; Wang, Semyung; Kindt, Peter; Pluymers, Bert; Desmet, Wim
Abstract: Natural frequencies, mode shapes and modal damping values are the most important parameters to describe the noise and vibration behavior of a mechanical system. For rotating machinery, however, the directivity of the propagation wave and the wave length of each mode should also be taken into account. Generally, the information on directivity and wave length is obtained on the basis of the mode shape result, which is estimated from several measurements measured at different locations. In this research, the accurate directivity and wave length results will be observed by calculating the phase difference at two different locations. The limitation of the proposed method, which arises from the difference between the assumed ring model and the real tire, will be explained, and a method to address the limitation is introduced. The proposed method is verified by applying it to experimental measurements, and a brief explanation of the obtained results is provided. Highlights: This paper is intended to provide wave number information and directivity information of a rolling tire for each mode. In this regards, we adopted a flexible rotating ring model to analyze dynamic behavior of a rotating tire. Base on this model, We proposed new technical approach to identify the directivity and number of wave length by using only 2 measurements of a rotating tire. We performed experiments to verify the proposed method. we selected 4 measurements among 45 measurements and we applied the proposed method to these selected measurements to identify the wave length and directivity information. We re-estimated mode shapes by using the identified information. We quantitatively compared these two results (mode shapes obtained from conventional approach vs. re-estimated mode shapes) through MAC value. From this comparison, we confirmed the reliability of the proposed method.